Distribution of Novel Og Types in Shiga Toxin-Producing Escherichia coli Isolated from Healthy Cattle - Nguyen, Thi Thu Huong (J Clin Microbiol, 2021)
Shiga toxin-producing Escherichia coli (STEC) is an important foodborne pathogen. Although most cases of STEC infection in humans are due to O157 and non-O157 serogroups, there are also reports of infection with STEC strains that cannot be serologically classified into any O serogroup (O-serogroup untypeable [OUT]). Recently, it has become clear that even OUT strains can be subclassified based on the diversity of O-antigen biosynthesis gene cluster (O-AGC) sequences. Cattle are thought to be a major reservoir of STEC strains belonging to various serotypes; however, the internal composition of OUT STEC strains in cattle remains unknown. In this study, we screened 366 STEC strains isolated from healthy cattle by using multiplex PCR kits including primers that targeted novel O-AGC types (Og types) found in OUT E. coli and Shigella strains in previous studies. Interestingly, 94 (25.7%) of these strains could be classified into 13 novel Og types. Genomic analysis revealed that the results of the in silico serotyping of novel Og-type strains were perfectly consistent with those of the PCR experiment. In addition, it was revealed that a dual Og8+OgSB17-type strain carried two types of O-AGCs from E. coli O8 and Shigella boydii type 17 tandemly inserted at the locus, with both antigens expressed on the cell surface. The results of this comprehensive analysis of cattle-derived STEC strains may help improve our understanding of the strains circulating in the environment. Additionally, the DNA-based serotyping systems used in this study could be used in future epidemiological studies and risk assessments of other STEC strains.